2021
DOI: 10.3389/fpos.2020.608203
|View full text |Cite
|
Sign up to set email alerts
|

Collective Protest and Expressive Action Among University Students in Hong Kong: Associations Between Offline and Online Forms of Political Participation

Abstract: Youth have often been described as politically apathetic or disengaged, particularly with respect to more conventional forms of participation. However, they tend to prefer non-institutionalized modes of political action and they may express themselves on the Internet. Young people have also been recognized as having a “latent preparedness” to get politically active when needed. This paper reports forms of offline and online participation adopted by young adults in Hong Kong who were surveyed shortly before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In the related literature, different concepts of political participation have been extensively discussed. Initially, research focused on electoral participation, that is, voting (Milbrath, 1965), but the Internet has opened new possibilities for citizens to engage in politics (Chadwick and Howard, 2008;Mossberger, Tolbert, and McNeal, 2008) and various forms of social media and online political participation activities have evolved (Kim and Hoewe, 2020;Reichert, 2021;Waeterloos, Walrave, and Ponnet, 2021). By now, the forms of political participation are continuously expanding, including activities such as boycotting, attending street parties, guerilla gardening, posting political blogs, joining flash mobs, signing petitions, or buying fair-trade products (Deth, 2016); these activities are typically conceived as unconventional forms of participation, while voting is often pondered as a conventional one (Ardèvol-Abreu, Gil de Zúñiga, and Gámez, 2020).…”
Section: Antecedents and Forms Of Political Participationmentioning
confidence: 99%
“…In the related literature, different concepts of political participation have been extensively discussed. Initially, research focused on electoral participation, that is, voting (Milbrath, 1965), but the Internet has opened new possibilities for citizens to engage in politics (Chadwick and Howard, 2008;Mossberger, Tolbert, and McNeal, 2008) and various forms of social media and online political participation activities have evolved (Kim and Hoewe, 2020;Reichert, 2021;Waeterloos, Walrave, and Ponnet, 2021). By now, the forms of political participation are continuously expanding, including activities such as boycotting, attending street parties, guerilla gardening, posting political blogs, joining flash mobs, signing petitions, or buying fair-trade products (Deth, 2016); these activities are typically conceived as unconventional forms of participation, while voting is often pondered as a conventional one (Ardèvol-Abreu, Gil de Zúñiga, and Gámez, 2020).…”
Section: Antecedents and Forms Of Political Participationmentioning
confidence: 99%
“…In the context of Hong Kong, recent studies suggest that youth have become increasingly active in non-institutionalized forms of political participation (Weiss, 2020) and they have a "latent preparedness" (Reichert, 2021) to become politically active when they are dissatisfied with the government and perceive themselves as being responsible to act against unjust laws. Reichert's (2021) study, based on university students, showed that the more students were involved in either online or offline political activities, the less satisfied they were with the government in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
“…Student demonstration is part of students' critical characteristics (Reichert, 2021;Revers & Traunmüller, 2020). Being critical is a general nature of students; it is why students are labeled critical activists.…”
Section: Discussionmentioning
confidence: 99%